Using EMBL‐EBI Services via Web Interface and Programmatically via Web Services. Issue 1 (12th December 2014) - Lopez, Rodrigo; Cowley, Andrew; Li, Weizhong; McWilliam, Hamish
Abstract: The European Bioinformatics Institute (EMBL‐EBI) provides access to a wide range of databases and analysis tools that are of key importance in bioinformatics. As well as providing Web interfaces to these resources, Web Services are available using SOAP and REST protocols that enable programmatic access to our resources and allow their integration into other applications and analytical workflows. This unit describes the various options available to a typical researcher or bioinformatician who wishes to use our resources via Web interface or programmatically via a range of programming languages. © 2014 by John Wiley & Sons, Inc.